Club position relative to the golfer's swing plane meaningfully affects swing dynamics - MacKenzie, S. J. (Sports Biomechanics, 2012)
Previous research indicates that the motion of the golf club is not planar and that the plane traced out by the club is different than that of the golfer's hands. The aim of the present study was to investigate how the position of the club, relative to the golfer's swing plane, influences the motion of the club by using a four-segment (torso, upper arm, forearm, and club), three-dimensional forward dynamics model. A genetic algorithm optimized the coordination of the model's four muscular torque generators to produce the best golf swings possible under six different conditions. The series of simulations were designed to demonstrate the effect of positioning the club above, and below, the golfer's swing plane as well as the effect of changing the steepness of the golfer's swing plane. The simulation results suggest that positioning the club below the golfer's swing plane, early in the downswing, will facilitate the squaring of the clubface for impact, while positioning the club above the plane will have the opposite effect. It was also demonstrated that changing the steepness of the golfer's swing plane by 10° can have little effect on the delivery of the clubhead to the ball.